PENERAPAN METODE PEMBELAJARAN ECLECTIC DALAM PENGAJARAN WRITING - Supiningsih Supiningsih (LP2M Universitas Sarjanawiyata Tamansiswa, 2018)
This study aims to determine the effect of Eclectic Learning Methods on English learning outcomes of students of Class X Busana Boutique 3 in SMK N 2 Gedangsari, Gunungkidul in the academic year 2017/2018 viewed from teaching writing. This research is a pseudo experiment. Techniques of collecting data using test techniques, questionnaires, and documentation. The instrument test contains 30 multiple choice questions, and the questionnaire instrument contains 20 statements. The result, the researchers obtained fcount = 1.94 and p = 3.37, the difference in average learning outcomes before treatment method and after was 15.7, the average questionnaire was 12.8. The percentage of students who have had KKM before and after treatment increased 79%, from 14% to 93%. Based on the average learning outcomes and questionnaires, then there is the influence of eclectic methods on learning outcomes of English students class X Busana Boutique 3 in terms of teaching writing.Keywords: eclectic learning model, learning outcomes, and teaching writing.